Patterns of helminth infections in Rattus rattus and Mus musculus from two Mayan communities in Mexico - Panti May, Jesús Alonso; Palomo Arjona, E. E.; Gurubel González, Y. M.; Barrientos Medina, R. C.; Digiani, Maria Celina; Robles, Maria del Rosario; Hernández Betancourt, S. F.; Machain Williams, Carlos (Journal of Helminthology)
The black rat Rattus rattus and the house mouse Mus musculus are two commensal rodent species that harbour and shed zoonotic pathogens, including helminths. The aim of this survey was to study the helminth community and the patterns of infections in R. rattus and M. musculus from two Mayan communities in Mexico. Gastrointestinal helminths were isolated from 322 M. musculus and 124 R. rattus, including Gongylonema neoplasticum, Hassalstrongylus aduncus, Hassalstrongylus musculi, Hydatigera taeniaeformis metacestode, Hymenolepis diminuta, Nippostrongylus brasiliensis, Oligacanthorhynchidae gen. sp., Syphacia muris, Syphacia obvelata, Rodentolepis microstoma and Trichuris muris. The overall richness of helminths was seven in R. rattus and six in M. musculus. The results of generalized linear models showed that juvenile rodents had lower probabilities of being infected with G. neoplasticum, H. taeniaeformis and H. musculi than adult rodents. A positive association between the prevalence of S. muris and rat abundance was found. The intensity of infection with S. muris was higher in the rainy season than in the dry season; the opposite result was found for H. musculi infection. Male R. rattus harboured more S. muris specimens. The intensity of infection with T. muris was inversely associated with mouse abundance. The presence of the zoonotic H. diminuta, as well as H. taeniaeformis and R. microstoma in rodent populations indicates that there is risk of transmission, and that their entire life cycle occurs in the study area. Fil: Panti May, Jesús Alonso. Universidad Autónoma de Yucatán; México Fil: Palomo Arjona, E. E. Universidad Autónoma de Yucatán; México Fil: Gurubel González, Y. M. Universidad Autónoma de Yucatán; México Fil: Barrientos Medina, R. C. Universidad Autónoma de Yucatán; México Fil: Digiani, Maria Celina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Invertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro ...